Convergence of dopamine and glutamate signaling onto striatal ERK activation in response to drugs of abuse - Cahill, Emma; Salery, Marine; Vanhoutte, Peter; Caboche, Jocelyne (Frontiers in Pharmacology, 2014)
Despite their distinct targets, all addictive drugs commonly abused by humans evoke increases in dopamine (DA) concentration within the striatum. The main DA Guanine nucleotide binding protein couple receptors (GPCRs) expressed by medium-sized spiny neurons of the striatum are the D1R and D2R, which are positively and negatively coupled to cyclic adenosine monophosphate (cAMP)/protein kinase A (PKA) signaling, respectively. These two DA GPCRs are largely segregated into distinct neuronal populations, where they are co-expressed with glutamate receptors in dendritic spines. Direct and indirect interactions between DA GPCRs and glutamate receptors are the molecular basis by which DA modulates glutamate transmission and controls striatal plasticity and behavior induced by drugs of abuse. A major downstream target of striatal D1R is the extracellular signal-regulated kinase (ERK) kinase pathway. ERK activation by drugs of abuse behaves as a key integrator of D1R and glutamate NMDAR signaling. Once activated, ERK can trigger chromatin remodeling and induce gene expression that permits long-term cellular alterations and drug-induced morphological and behavioral changes. Besides the classical cAMP/PKA pathway, downstream of D1R, recent evidence implicates a cAMP-independent crosstalk mechanism by which the D1R potentiates NMDAR-mediated calcium influx and ERK activation. The mounting evidence of reciprocal modulation of DA and glutamate receptors adds further intricacy to striatal synaptic signaling and is liable to prove relevant for addictive drug-induced signaling, plasticity, and behavior. Herein, we review the evidence that built our understanding of the consequences of this synergistic signaling for the actions of drugs of abuse.